Of Links and Legal Merits: Good Faith in the Statutory Derivative Action in Singapore - KOH, Pearlie M. C. (Institutional Knowledge at Singapore Management University, 2015)
An applicant for leave to bring a statutory derivative action in Singapore is required to satisfy the court as to, inter alia, his good faith. Although the statutory language places the burden of doing so on the applicant, Singapore courts have tended to assume the presence of good faith if the claim is a legitimate one. This approach, which denigrates the requirement of good faith, was recently disapproved by the Singapore Court of Appeal. This notwithstanding, subsequent cases have reverted to the earlier position, casting doubt on the utility of the requirement. This paper considers good faith, and argues that it was included to address a distinct concern that cannot be met by a consideration of the viability of the claim and the company's interests in pursuing the same, a concern that arose out of the peculiar function of the statutory derivative action in opening up shareholder access to corporate litigation.